Hubungan umur dan paritas dengan penggunaan metode kontrasepsi pada akseptor keluarga berencana - Siti Shafidha Hidayah; Asmar Yetty Zein; Sabar Santoso (Poltekkes Kemenkes Yogyakarta, 2013)
In mid 2010, Indonesia is the country with the largest population among member states of ASEAN. The government has a program in family planning to curb population growth. Based of the data from BKKBN Yogyakarta, of 14 district in the city of Yogyakarta, Ngampilan District a district with the lowest prevalence rate family planning is 61,80% . This study purpose to determine the correlation of age and parity to the contraceptive method used in family planning acceptors. The study was an observational analytic study with cross sectional approach. The number of respondents were 188 family planning acceptors. This analysis with univariable, and bivariable by using chi square. Result group of low risk are used KB Non-MKJP 98 respondents (96,1%.) and 4 respondents (3,9%) are used MKJP (p-value 0,004). Age can improve methods contraceptive use (RP 4.764, 95% Cl 1.505 - 15.077), parity multiparous are used Non-MKJP 162 respondents (92,6%), and 13 respondents (7,4%) are used MKJP (p-value 0,000). Parity can improve methods contraceptive use (RP7.788,95% Cl 2.227 - 27.241). conclusion there is a significant correlation between age and parity with the contraceptive method used in family planning acceptors, result showed age to be factor who can improve methods contraceptive use 4.764, and parity can improve methods contraceptive use 7.788.